The Influence Of Work Environment And Work Discipline On Employee Performance (Survey at the HSB Ban Tasikmlaya workshop): Alwin Fralesta Nugraha, Barin Barlian, Ai Kusmiati Asyiah - Nugraha, Alwin Fralesta; Barlian, Barin; Asyiah, Ai Kusmiati (Utami Publisher, 2025)
This research purposse to determine and analyze the description of work environment, work discipline and employee performance at the HSB Ban Tasikmalaya. The Simultaneous Influence of Work Environment and Work Discipline on the Employees Perfomance at the HSB Ban Tasikmalaya. As well as the partial influence of work environment and work discipline on the employee performance at the HSB Ban Tasikmalaya. The method used in this research is descriptive quantitative. With a research sample of 32 as respondents. The data used is primary and secondary data. The analytical tool used in this research is multiple linear regression using the SPSS version 26 support application. The results of the research show that work environment at the HSB Ban Tasikmalaya is qualified in the very good category, for the work discipline of employees at the HSB Ban Tasikmalaya it can be said to have high criteria, and for the employee perfromance at the HSB Ban Tasikmalaya is also in very good. The results of the hypothesis test show that simultaneously the variables used in the research, namely work environment and work discipline, have a significant effect on the employee performance at the HSB Ban Tasikmalaya. But, this research partially shows that work environment has no effect significant influence of employee performance, and partially there is a significant influence of work discipline on the employee performance at the HSB Ban Tasikmalaya.